The plight of the Tharu Kamaiyas in Nepal: A review of the social, economic and political facets - Chhetri, Ram B (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 3,160 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v9i0.1134 Occasional Papers in Sociology and Anthropology Vol.9 2005 p.22-46